The Importance of Exchange Rate Policy in Promoting Vietnam's Exports - Nguyen, Ngoc Thach (ĐHKT, 2016)
The analysis in this paper shows that, during the 1990s, the use of tariffs, quotas and export price policy by the State Bank of Vietnam was more effective than devaluation in controlling imports in both the short term and long term, but encouraged Vietnamese exports only in the short term. Given the need for Vietnam to integrate with other economies, particularly with the ASEAN countries, the results suggest an appropriate exchange rate policy should be instituted to achieve export growth consistently in the long run rather than depending on tariffs and quotas.